(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: The rapid socio-economic development in Bhutan has brought changes in individual lifestyles resulting in increased risk behavior of the urban population, particularly the Drayang girls. This study investigated the underlying factors influencing the sexual risk behaviour of Drayang girls and their vulnerability to HIV and Sexually Transmitted Infection (STI). The Drayangs are dance bars in Bhutan where the women perform Bhutanese songs/dances on the stage to entertain the bar patrons and making them pay for their performance. Methods: This is a cross-sectional descriptive study conducted from May-July 2015 in three urban districts (Thimphu, Paro, and Phuentsholing) of Bhutan. The convenient non-random sampling method was used to recruit the respondents. We have collected the data using structured questionnaires including the taking of blood samples for HIV, Hepatitis B, and Syphilis testing. Results: Of the 245 Drayang girls recruited for this study, 28.2% have engaged in transactional sex and 71.8% in non-transactional sex within last month. Condom use during transactional sex was 36.2% and non-transactional sex was 21.6%. The prevalence of HIV was 0.82%, hepatitis B 6.9%, and syphilis 2.8%. The factors such as marital status (divorced and unmarried), living arrangements, current living cities, and alcohol consumption were significantly (p<0.05) associated with transactional sex among Drayang girls. Conclusion: Although the prevalence of HIV and STIs is low among the Drayang girls, the presence of high riskbehavior with low condom use still makes them vulnerable to HIV and STIs. The study recommends putting more effort in prevention of HIV and STI by increasing awareness of HIV and STI, targeted interventions like Behaviour Change Communications (BCC), condom promotion, condom negotiation skills and access for testing and treatment of HIV and STI.